Integrated charge excitation triboelectric nanogenerator - Wenlin Liu (Nature Portfolio, 2019)
Triboelectric nanogenerators may benefit Internet-of-Things era energy demands, but application is hindered by low charge density. Here the authors maximize charge density in ambient conditions and achieve stable power generation in a triboelectric nanogenerator that can realize external and self-excitation.